2013
DOI: 10.1177/0956462413516301
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of non-adherence to antiretroviral therapy in a cohort of HIV-positive drug users receiving antiretroviral therapy in Hanoi, Vietnam

Abstract: The HIV epidemic in Vietnam is concentrated, with high prevalence estimates among injection drug users and commercial sex workers. Socio-demographics, substance use and clinical correlates of antiretroviral therapy non-adherence were studied in 100 HIV-1 infected drug users (DUs) receiving antiretroviral therapy (ART) for at least 6 months in Hanoi, Vietnam. All study participants were men with a mean age of 29.9 ± 4.9 years. The median duration on ART was 16.2 ± 12.7 months. 83% reported ‘very good’ or ‘perfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 27 publications
1
19
1
2
Order By: Relevance
“…The previously reported association between suboptimal treatment adherence among former and current IDU, compared to non-IDU may be a key explanation for this finding in our study,24 especially given evidence that most IDU continue to inject drugs even after initiating ART 25–27. Nevertheless, our study did not provide information on the current injecting drug-use status.…”
Section: Discussioncontrasting
confidence: 53%
“…The previously reported association between suboptimal treatment adherence among former and current IDU, compared to non-IDU may be a key explanation for this finding in our study,24 especially given evidence that most IDU continue to inject drugs even after initiating ART 25–27. Nevertheless, our study did not provide information on the current injecting drug-use status.…”
Section: Discussioncontrasting
confidence: 53%
“…With improved tolerability and convenience using contemporary ART regimens, evidence from both high 45 and LMIC 46 confirm improved short-term adherence among PWUD; from 1996 to 2009, >95% adherence increased from 19.3% to 65.9% in Canada. 47 Longer studies, however, suggest that a substantial proportion of PWUD either discontinue treatment or have sub-optimal adherence.…”
Section: Challenges In Treatment Access and Care Retentionmentioning
confidence: 97%
“…The majority of the included quantitative studies indicated that illicit drug use significantly and negatively affected HIV‐positive drug users’ adherence to HAART . A longitudinal study conducted in New York by French et al .…”
Section: Resultsmentioning
confidence: 99%